Pemberdayaan Perempuan Muda Hindu Melalui Bengkel Penulisan Esai Sebagai Upaya Penguatan Literasi dan Ekspresi Intelektual - Yani, Ni Luh Sinta; Sari, Puji Novita; Paramita, Septiannisa; Azis, Maghfirah Sari; Alrizqi, Damas Gianlugi (Jurnal Bina Desa, 2025)
This community service program aims to empower young Hindu women through an essay writing workshop as an effort to strengthen literacy and intellectual expression. The background of this activity lies in the low ability of young Hindu women to write essays systematically, despite their high interest in writing. The method applied was Participatory Action Research (PAR), consisting of several stages: needs identification, activity planning, workshop implementation, reflection, evaluation, and follow-up in the form of publication of participants’ works. The program was carried out over eight weeks and involved young Hindu women facilitated by KMHDI. The results indicated significant improvement in participants’ literacy skills, particularly in essay structure, argumentation, and confidence in presenting ideas. Several participants successfully produced their first essays, some of which were published in KMHDI’s internal media. The implication of this program is the creation of a space for actualization that encourages young Hindu women to become more critical, reflective, and active in contributing to intellectual public discourse.